Cartography of an Event: On the Visuality of the Map in (Neo)conceptual Art - Ján Kralovič (Sociální studia, 2016)
The article deals with the map as an image whose visuality within the framework of conceptual artists claims a strategy or a map image based upon the records of their activities. Maps are not understood as objective, technical transcriptions of topographic structures, but in relation to artistic production – as records of creative presence and subjective perception, recording locations and their specifics. Maps represent a scene where disparate elements are brought together and form an image of a particular state of knowledge. In this text the use of maps is analyzed on two basic levels: a) the map as a result (record) of a mental or physical process, and b) the map as the documentation of an activity that was part of spatial practice in a specific territory. Selected examples of artists and their works are given, based on a conceptual (appropriation, dematerialization, concept / idea accentuation) character in the period of the 1960s through the 1990s (namely M. Šejn, D. Tóth, Ľ. Ďurček, R. Matuštík, M. Maur, and M. Adamčiak) with forays into contemporary neo-conceptual strategies (such as those of J. Pfeiffer).